1999
DOI: 10.1021/ic990276b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray Crystal Structure of [CuIN(R2PS)2]3

Abstract: Simple one-stage reactions of dithioimidophosphinates with CuCl or CuCl2 give trinuclear copper complexes [CuIR2P(S)NHP(S)R‘2]3 which contain Cu3S3 cores. Nonsymmetrical ligands coordinate to give isomers with or without pseudo-3-fold symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…The X-ray structure of 23c revealed that it is trimeric like the corresponding sulfur and selenium complexes, respectively (Fig. 10) [29,27]. However, the tellurium derivative 23c exhibits significant structural differences compared to 23a and 23b, in which all three ligands are coordinated to the copper centres via one two-coordinate and one three-coordinate chalcogen atom.…”
Section: Figurementioning
confidence: 99%
“…The X-ray structure of 23c revealed that it is trimeric like the corresponding sulfur and selenium complexes, respectively (Fig. 10) [29,27]. However, the tellurium derivative 23c exhibits significant structural differences compared to 23a and 23b, in which all three ligands are coordinated to the copper centres via one two-coordinate and one three-coordinate chalcogen atom.…”
Section: Figurementioning
confidence: 99%
“…[1] A literature survey reveals that there have been some studies on the reaction of L with Cu II salts, and these have led to the synthesis of complexes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability of L to form a tetrahedral CuS 4 core with the Cu II ion has been used by Bereman et al [3] to propose the complex [Cu(L) 2 ] as a potential model for type-I Cu II sites in metalloenzymes; unfortunately, the complex was not stable for more than a few days at room tempera- form a slightly distorted tetrahedral CuS 4 core. The 31 P NMR spectroscopic data of compound 1 are consistent with the maintenance of its structure in solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations